Evaluation of subclinical atherosclerosis in Egyptian psoriatic patients - Elsheikh, Raghda Ghonimy (2013)
BACKGROUND: Psoriasis (Ps) is a common, relapsing, immune-mediated, inflammatory skin disorder of unknown etiology. Ps is not single organ disease confined to the skin but it is systematic inflammatory condition analogous to other inflammatory immune disorders which are known to have increased risk of heart disease. On other hand, inflammation plays also an important role in the pathogenesis of atherosclerosis. So, there is striking similarity between molecular and inflammatory pathway in Ps and atherosclerosis. AIM OF THE WORK: Was to assess the presence of subclinical atherosclerosis in patients with Ps by using carotid ultrasonography. PATIENTS AND METHODS: 60 patients with Ps were enrolled in this study after exclusion of traditional cardiovascular risk factors and cardiovascular diseases (CVD). In addition, 20 age and gender matched healthy persons served as controls. Patients were classified according to Ps area and severity index (PASI) score into group I (20 mild patients), group II (20 moderate) and group III (20 severe). The average common carotid artery (CCA) intima media thickness (IMT), internal diameter (ID) and arterial wall mass index (AWMI) were measured using high resolution B- mode ultrasound. RESULTS: Psoriatic patients showed statistically significant increase in CCA-IMT (P value 0.001), AWMI (P value 0.010) and significant decrease in ID (P value 0.001), as compared to controls. CONCLUSION: Psoriasis patients could be suggested as a group with an increased atherosclerotic risk especially in older ages with longer duration of Ps. The carotid IMT, ID and AWMI can identify patients with subclinical atherosclerosis who need special follow up to reduce cardiovascular morbidity and mortality.